Roles of PPAR transcription factors in the energetic metabolic switch occurring during adult neurogenesis. Issue 1 (2nd January 2017) - Di Giacomo, E.; Benedetti, E.; Cristiano, L.; Antonosante, A.; d'Angelo, M.; Fidoamore, A.; Barone, D.; Moreno, S.; Ippoliti, R.; Cerù, M. P.; Giordano, A.; Cimini, A.
ABSTRACT: PPARs are a class of ligand-activated transcription factors belonging to the superfamily of receptors for steroid and thyroid hormones, retinoids and vitamin D that control the expression of a large number of genes involved in lipid and carbohydrate metabolism and in the regulation of cell proliferation, differentiation and death. The role of PPARs in the CNS has been primarily associated with lipid and glucose metabolism; however, these receptors are also implicated in neural cell differentiation and death, as well as neuronal maturation. Although it has been demonstrated that PPARs play important roles in determining NSCs fate, less is known about their function in regulating NSCs metabolism during differentiation. In order to identify the metabolic events, controlled by PPARs, occurring during neuronal precursor differentiation, the glucose and lipid metabolism was followed in a recognized model of neuronal differentiation in vitro, the SH-SY5Y neuroblastoma cell line. Moreover, PPARs distribution were also followed in situ in adult mouse brains. The concept of adult neurogenesis becomes relevant especially in view of those disorders in which a loss of neurons is described, such as Alzheimer disease, Parkinson disease, brain injuries and other neurological disorders. Elucidating the crucial steps in energetic metabolism and the involvement of PPARγ in NSC neuronal fate (lineage) may be useful for the future design of preventive and/or therapeutic interventions.